2020
DOI: 10.1186/s12894-020-00679-2
|View full text |Cite
|
Sign up to set email alerts
|

The neutrophil-lymphocyte ratio has a role in predicting the effectiveness of nivolumab in Japanese patients with metastatic renal cell carcinoma: a multi-institutional retrospective study

Abstract: Background: The neutrophil-lymphocyte ratio (NLR) is a well-known prognostic marker in various cancers. However, its role as a predictive marker for the effectiveness of nivolumab in patients with metastatic RCC (mRCC) remains unclear. We evaluated the relationships between the NLR and progression-free survival (PFS) or overall survival (OS) in mRCC patients treated with nivolumab. Methods: The data of 52 mRCC patients who received nivolumab therapy were collected from seven institutes and evaluated. The media… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“… 14 , 15 Similar studies on inflammatory indices in mRCC treated with nivolumab reported comparable results; however, it should be noted that they are mainly monocentric analysis investigating only one or few indices in a lower number of patients. 4 , 26 38 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 14 , 15 Similar studies on inflammatory indices in mRCC treated with nivolumab reported comparable results; however, it should be noted that they are mainly monocentric analysis investigating only one or few indices in a lower number of patients. 4 , 26 38 …”
Section: Discussionmentioning
confidence: 99%
“…In the era of ICIs, inflammatory indices have mostly been studied in advanced melanoma and non-small lung cancer patients, 17 21 while fewer and smaller studies have been conducted in patients treated with immunotherapy for genitourinary tumors, 22 25 including mRCC. 4 , 26 38 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After examining titles and abstracts, 19 studies were identified. A total of seven studies had insufficient data following a full-text review, leaving 12 records included according to the eligibility criteria (Figure 1) (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). The literature search was performed by two investigators, and any disagreements between them were settled by consensus.…”
Section: Literature Characteristicsmentioning
confidence: 99%
“…Currently, although several studies have explored the prognostic value of NLR in patients receiving immunotherapy for RCC (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28), it is still difficult to verify the prognostic role of NLR in patients with RCC treated with ICIs. Certain studies have suggested that the NLR is not associated with the prognosis of patients with RCC treated with immunotherapy (21,26). Additionally, some of the published studies had a small sample size (17,18,28).…”
Section: Introductionmentioning
confidence: 99%